PEMANFAATAN METODE SUMI UNTUK ANALISIS KEGUNAAN APLIKASI SI ELANG BPAD PROVINSI NTT - Meak, Melania Yora; Igon, Skolastika Siba (Lembaga Pengembangan Kinerja Dosen, 2026)
The use of information technology in public services is increasingly becoming a primary need to support transparency and efficiency in government agencies. One implementation is the SI ELANG application developed by the Regional Revenue and Asset Agency (BPAD) of East Nusa Tenggara Province. Data was obtained through questionnaires distributed to active users of the application, namely BPAD civil servants within the NTT Provincial Government. With the increasing number of vehicles and the complexity of traffic, the public often faces difficulties in accessing information related to tax obligations and ticketing processes. As a solution, this study utilized the SUMI (Software Usability Measurement Inventory) method to measure the usability of the SI ELANG application. This method measures five main aspects of usability: Efficiency, Affect (emotional satisfaction), Helpfulness, Control, and Learnability. This study aims to evaluate the usability of the SI ELANG application using the SUMI (Software Usability Measurement Inventory) method, which covers five aspects: Efficiency, Affect, Helpfulness, Control, and Learnability. The results indicate that, in general, the SI ELANG application has a good level of usability, with an average usability score of 3.69 out of a maximum scale of 4.00. All usability aspects were rated positively by users, although there was still a slight gap from ideal expectations, particularly in the efficiency aspect. The SUMI method proved effective in providing a comprehensive overview of user perceptions of the application's ease and convenience.